Evaluasi Program Bimbingan dan Konseling - Hidayat, Arifin Hidayat (Institut Agama Islam Negeri Padangsidimpuan, 2020)
AbstractÂ Essentially the implementation of guidance and counseling can help counselees in changing behavior for the better. So that in the implementation of counseling guidance must be evaluated systemically, so that the implementation can be directed and measured, and can be seen the results of the implementation of the guidance and counseling, but in reality there are still some guidance and counseling implementation that is not properly evaluated and uses applicable standards. This paper aims to describe the implementation of the guidance and counseling program evaluation. So it appears an increase in the implementation of counseling. As for the findings in this paper, the evaluation carried out must involve relevant and influential elements, as well as get feedback from those evaluated, then what is evaluated in the guidance and counseling program is the process evaluation and evaluation of the results of the guidance and counseling program.